Mesenchymal Stem Cells Promoted Lung Wound Repair through Hox A9 during Endotoxemia-Induced Acute Lung Injury - Xi Xin; Liu Yan; Zhu Guangfa; Huang Yan; Li Keng; Wu Chunting (Stem Cells International)
Objectives. Acute lung injury (ALI) is a common clinical critical disease. Stem cells transplantation is recognized as an effective way to repair injured lung tissues. The present study was designed to evaluate the effects of mesenchymal stem cells (MSCs) on repair of lung and its mechanism. Methods. MSCs carrying GFP were administrated via trachea into wild-type SD rats 4 hours later after LPS administration. The lung histological pathology and the distribution of MSCs were determined by HE staining and fluorescence microscopy, respectively. Next, differentially expressed HOX genes were screened by using real-time PCR array and abnormal expression and function of Hox A9 were analyzed in the lung and the cells. Results. MSCs promoted survival rate of ALI animals. The expression levels of multiple HOX genes had obvious changes after MSCs administration and HOX A9 gene increased by 5.94-fold after MSCs administration into ALI animals. HOX A9 was distributed in endothelial cells and epithelial cells in animal models and overexpression of Hox A9 can promote proliferation and inhibit inflammatory adhesion of MSCs. Conclusion. HoxA9 overexpression induced by MSCs may be closely linked with lung repair after endotoxin shock.